Adaptation and validation of a rubric for teamwork skills in collaborative learning - Martínez-Venegas, Liliana; Gaytán Lugo, Laura Sanely; Hastie, Carolyn Ruth (IE Revista de Investigación Educativa de la REDIECH, 2023)
TeamUp is a rubric for evaluating teamwork skills in a collaborative learning context in face-to-face and virtual environments. This work presents the adaptation and validation process of TeamUp for Mexican high school students. First, the TeamUp rubric was translated into Spanish, afterward, a validation was conducted with five expert judges, who evaluated the translated rubric using various criteria. The calculation of the content validity coefficient placed 23 items at a good level of validity and agreement (³ 0.8), while the remaining 10 had an excellent level in the same categories (³ 0.9). The Cronbach’s Alpha coefficient calculated with responses from 309 high school students showed that TeamUp has high reliability (> 0.9). The results reflected by TeamUp in this work present it as a robust proposal for teaching and developing teamwork skills for adolescents in collaborative learning. The Spanish used in this rubric is suitable for Mexican adolescents, and future adaptations suggest modifying the language for the audience of other Spanish-speaking regions.